Analysis of Factors Associated with Pregnant Women’s Adherence in Consuming Iron (Fe) Tablets - Sevania, Nabila; Dewi Woro Astuti; Aila Karyus (CV. CENDIKIA JENIUS INDONESIA, 2025)
Anemia in pregnant women remains a major public health problem that increases the risk of pregnancy complications, childbirth difficulties, as well as maternal and infant mortality. One preventive effort is the provision of iron (Fe) tablets; however, adherence to consumption among pregnant women is still low. This study aims to analyze the factors associated with pregnant women’s adherence in consuming Fe tablets at Kedaton Public Health Center, Bandar Lampung City in 2025.This research employed a cross-sectional design with a quantitative approach. The study population consisted of 334 pregnant women who underwent antenatal examinations from January to April 2025, with a sample of 77 respondents selected through simple random sampling. Data were collected using a structured questionnaire and analyzed using the chi-square test with a 95% confidence level (α=0.05).The results showed that age (p=0.000), education (p=0.045), knowledge (p=0.009), attitude (p=0.022), and husband’s support (p=0.009) were significantly associated with adherence to Fe tablet consumption. The majority of non-compliance was caused by limited knowledge and low awareness of the benefits of iron supplementation.In conclusion, age, education, knowledge, attitude, and husband’s support significantly influence adherence to Fe tablet consumption. It is recommended that health workers strengthen nutrition education programs and involve families in supporting pregnant women to improve adherence and reduce the risk of anemia.